Strategi Manajemen Keuangan Keluarga Muslim Dalam Perspektif Syariah Di Era Digital - Muhammad Amsal Nasution; Khoirun Nisa Zein Lubis; Amhar Maulana Harahap; Eva Zuliani Munthe; Nurdiana Lubis; Aisyah Tilawatinnur Hsb (Yayasan Salam Cerdas Al-Fattah, 2025)
This research was conducted among the residents of Paranbatu Village, Padang Lawas Regency, who work primarily as farmers and traders. During the lean season, they continue to meet their daily needs, such as clothing, food, and shelter. In addition, they strive to save and invest to secure their future needs. The study aims to examine how the people of Paranbatu Village manage their family finances from an Islamic perspective. This research employs a qualitative approach with a field research design. The participants were selected purposively, and data were collected through observation, interviews, and documentation. The findings reveal that the family financial management strategies include financial planning, saving, investment, and zakat. However, these efforts still face various obstacles and challenges, indicating the need for stronger cooperation among family members to realize the ideal of a sakinah (harmonious and prosperous) family.